Trade in the Shadow of Power: Japanese Industrial Exports in the Interwar years - Alejandro Ayuso-Díaz; Antonio Tena-Junguito (European Historical Economics Society (EHES), 2019)
During the interwar years, Japanese industrialisation accelerated alongside the expansion of industrial exports to regional markets. Trade blocs in the interwar years were used as an instrument of imperial power to foster exports and as a substitute for productivity to encourage industrial production. The historiography on Japanese industrialisation in the interwar years describes heavy industries' interests in obtaining access to wider markets to increase economies of scale and reduce unit costs. However, this literature provides no quantitative evidence that proves the success of those mechanisms in expanding exports. In this paper we scrutinise how Japan—a relatively poor country—used colonial as well as informal power interventions to expand regional markets for its exports, especially for the most intensive human capital sector of the industrializing economy.
Keywords: F14; N15; N75; 330; International Trade; Empires; Trade blocs; Japan; Interwar years